Transformasi Peran Pendidik di Era Digital - Sugiyanto; Lisnawati, Alis; Bagavadgitha, Aulia; Shopatunnisa, Nazwa; Rahmawati, Tri Nita (Universitas Cokroaminoto Yogyakarta, 2025)
This research transforms teaching from a traditional paradigm that focuses on teachers to a student paradigm in the digital era. With the advent of digital technology and artificial intelligence (AI), teachers are expected to develop their digital, pedagogical, and social skills so that they can facilitate relevant, interactive, and individualized learning. digital technology and artificial intelligence (AI), teachers are expected to develop their digital, pedagogical, and social skills so that they can facilitate relevant, interactive, and individualized learning. The role of teachers is to facilitate, train, and collaborate by integrating technologies, such as learning management systems (LMS), artificial intelligence (AI), and other digital platforms, to enhance hybrid learning and student character development. train, and collaborate by integrating technologies, such as learning management systems (LMS), artificial intelligence (AI), and other digital platforms, to enhance hybrid learning and student character development. Transformation is carried out by governments and educational institutions through continuous teaching, digital infrastructure, and accessible government technology. educational institutions through continuous teaching, digital infrastructure, and accessible technology. Teachers also act as AI-based learning orchestrators who maintain ethical and humanitarian aspects and as digital literacy agents who equip students with the ability to think critically about digital information. This study shows the evolution of the increasingly complex and strategic role of educators, as well as the need for policy support and training to ensure that digital education transformation runs optimally, inclusively, and sustainably.